PERLINDUDNGAN HUKUM PEMILIK HAK ATAS TANAH ATAS KEPEMILIKAN SERTIFIKAT TANAH ELEKTRONIK DEMI MEWUJUDKAN KEPASTIAN HUKUM - Firoos Atha Wafii (NOVUM : JURNAL HUKUM, 2014)
The electronic land certificate (STE) is an electronic document generated from the implementation of electronic land registration, initiated by the Ministry of Agrarian Affairs as part of efforts to improve land services. This study aims to analyze the legal protection for landowners regarding the ownership of electronic land certificates (STE) in ensuring legal certainty. The electronic land certificate is an innovation by the National Land Agency (BPN) to enhance efficiency and transparency in land administration. However, the implementation of STE has raised public concerns regarding data security and legal certainty. This research employs a normative juridical method with a statutory and conceptual approach. The findings indicate that STE has the same legal force as analog land certificates, as regulated in the Basic Agrarian Law (UUPA), Government Regulation No. 24 of 1997, and Ministerial Regulation ATR/BPN No. 3 of 2023. However, there are still deficiencies in specific regulations governing the security of STE data. BPN has implemented various security measures, such as data encryption, electronic signatures, and ISO 27001:2013 standards, and plans to adopt blockchain technology to enhance data security. Nevertheless, a specific law regulating STE and data protection in detail is needed to provide stronger legal certainty. This study concludes that STE is a positive step in improving land services, but further development is necessary in regulatory and data security aspects to ensure optimal legal protection for landowners Keyword: Electronic Land Certificate, Legal Protection, Legal Certainty, Data Security, Blockchain